The Study of AI-Mediated Communication and Socio-Cultural Language-Related Variables: Gmail Reply Suggestions - Sami Algouzi; Ali Abbas Falah Alzubi (Applied Artificial Intelligence, 2023)
The current research describes the use of e-mail reply suggestions from a socio-cultural perspective of some language-related variables. It also correlates how users perceive the use of e-mail reply suggestions to some variables: job, specialization, age, and gender. In this descriptive-inferential survey design, a self-developed questionnaire was distributed online to collect the data from a convenient sample of e-mail users. The analysis shows the study sample perceived medially the use of e-mail reply suggestions. There are statistically significant differences in the respondents’ means about using e-mail reply suggestions according to the variable of job for education, specialization for humanities, and gender for females. Also, ages of less than 30 and above 50 years are of significance in using e-mail reply suggestions. The study reveals a weak inverse correlation, however, statistical between using e-mail reply suggestions and the language of those suggestions. In addition, a statistically significant positive direct correlation is found between usability and culture and society of e-mail reply suggestions. In light of the findings, the study recommends the better implementation of artificial intelligence-mediated communication in e-mail reply suggestions in association with some sociolinguistic factors. Also, future related studies are suggested.